2007
DOI: 10.1007/s11920-007-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Late-life depression and alcoholism

Abstract: The relationship between alcohol use and later-life depression is complex. At-risk and problem drinking elevates the risk of depressive symptoms. The co-occurrence of alcohol use disorders and depression increases the potential for poor mental and physical health outcomes in older adults. Many older adults who are experiencing problems related to alcohol use do not meet alcohol abuse/dependence criteria. Depressive symptoms among older adults often are overlooked or misdiagnosed. The role of at-risk and proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 48 publications
0
31
0
4
Order By: Relevance
“…Due to the complex nature of alcoholism, numerous definitions exist; however, a widely accepted definition of this condition that could be used in different medical fields has not been developed yet (1,2). According to Jellinek (3), alcoholism is every use of alcohol harmful to the individual, society, or both (3).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex nature of alcoholism, numerous definitions exist; however, a widely accepted definition of this condition that could be used in different medical fields has not been developed yet (1,2). According to Jellinek (3), alcoholism is every use of alcohol harmful to the individual, society, or both (3).…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of 14,063 Canadian residents using four types of alcohol measures (frequency, usual and maximum quantity per occasion, volume, and heavy episodic drinking) and two types of depression measures (major depression, and recent depressed affect) Graham et al, 2007 revealed that major depression was primarily related to drinking large quantities of alcohol per occasion, less related to drinking volume and unrelated to drinking frequency. In another study Blow et al [27] reported that individual's at-risk and problem drinking elevated the risk of depressive symptoms. Results of a fourteen years longitudinal study revealed that at the baseline and 14-year follow-up alcohol consumption was linearly and positively associated with depressive symptoms; prevalence of symptoms increased with greater alcohol consumption [28].…”
Section: Discussionmentioning
confidence: 98%
“…Con respecto a la etiología de la PD en esta población, se ha reportado que factores como la muerte de seres queridos, las enfermedades médicas, la pérdida del trabajo y el retiro, pueden influir negativamente en el estado de ánimo y en el consumo de alcohol (Blow & Barry, 2003;Blow, Serras, & Barry, 2007). Un estudio realizado en población general de la tercera edad en México identificó que el diagnóstico de una o más enfermedades concurrentes aumenta las probabilidades de presentar consumo de sustancias (Mendoza-Meléndez et al, 2015).…”
Section: Epidemiologíaunclassified
“…Los TCS y OTP en esta población incrementan el riesgo de padecer enfermedades crónico-degenerativas (como diabetes mellitus, cataratas, ceguera, glaucoma, úlcera duodenal y cáncer, entre otras), enfermedades infecciosas, problemas de sueño y de memoria, y demencias (Aguilar-Navarro & Ávila-Funes, 2007; Blow & Barry, 2003;Blow et al, 2007;Caputo et al, 2012;Mendoza-Meléndez et al, 2015).…”
Section: Implicaciones De Salud Públicaunclassified
See 1 more Smart Citation